Konflik Sosial ‘Pembongkaran Urban’ Pada Pembangunan Fly Over Simpang Surabaya Banda Aceh - Nurkhalis Nurkhalis (Prodi Sosiologi FISIP Universitas Teuku Umar, 2017)
Several types of space were introduced Henri Lefebvre's, among them, the absolute space which is created by God, covering its environment), the abstract space as a tool of power, the practice of power), the natural space which is green space that has a positive effect on the welfare and prosperity of the people. Finally, the differential space which is the more diffuse space (merging of space) in order to restore the unity of people in it. From some space concepts according to Lefebvre, it appears that the construction of the mega project of Simpang Surabaya Fly Over cost up to Rp 250 billion from the Central Goverment (Jakarta) -has 850 meters in length and divided into 8 stretches targeted to be done by December 2017 -as the reproduction of space which belongs to abstract space. It is proven that after several months of construction starting in August 2016, a number of shops and micro businesses (such as tollers, sandal and shoes traders, snack vendors on the sidewalks) began to close. Responding to these conditions, it is deserved to be called 'urban demolition'. The term urban demolition is the situation or condition of the destruction of the poor (micro entrepreneurs). Ultimately, spatial practice (space) of development is supposedly served as the abstract space fosters the system of capitalism, the recognition of the status of the elite class, the widespread commodities consumed, the supernatural economic base and politically important. This article raises one important issue,, what is the actual practice of spatial arrangement formed in the case of the construction of the mega project of Simpang Surabaya Fly Over Banda Aceh. Secondly, the construction of Simpang Surabaya Fly Over and Simpang Beurawe Underpass make the local government more aligned to the public (the people of Aceh) or precisely to the capitalist / industrial investors. The two problems are analyzed using socio-spatial approach where the research uses qualitative approach descriptively. In short, this study tries to trace the usefulness of the reduced space into a quandary space in its construction between constructive and deconstructive. Keywords: Construction, Spatial, City, Urban